Il piccolo garibaldino and Le medaglie di Bidoni: Gender and Nationalism Performed Across Genres in Early Italian Cinema. (4th May 2019) - Boylan, Amy
ABSTRACT: This article looks at two films produced by Cines in the years preceding the First World War, Il piccolo garibaldino (1909) and Le medaglie di Bidoni (1912), in order to highlight particular ways in which nationalist ideas about war and gender circulating during the Risorgimento were adapted to new contexts, new wars, and a new medium, and across narrative genres. Additionally, the article explores how these new cinematic articulations of Italian nationalism exposed some uncomfortable contradictions about acceptable wartime roles for men and women.